Qur'anic Ideal Families: Imran and Ibrahim in Al-Zuhaili and Al-Manar Tafsirs - Kholiq, Abdul (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
The family is the basic unit of society in Islam, playing a strategic role in shaping a generation of believers and the pious. Modern challenges such as shifting values, individualism, and globalization demand a deep understanding of the Qur'anic guidance regarding the ideal family. This study explores the stories of the families of Imran and Ibrahim, which emphasize the values of monotheism, spiritual education, sacrifice, and exemplary behavior in raising children. Referring to the exegeses of al-Manar and al-Munir, these Qur'anic teachings are analyzed to build a harmonious and pious family capable of facing the challenges of the contemporary era. This study aims to describe the concept of the ideal family in the Qur'an through the stories of the families of Imran and Ibrahim based on the exegeses of al-Manar and al-Munir. The research employs a qualitative method with a semiotic approach. Primary data consists of Qur'anic verses, based on the interpretations of al-Manar and al-Munir. Data collection techniques include literature study and document analysis. The results of this study found that the Qur'an depicts the families of Imran and Ibrahim as ideal models with values of monotheism, education, and sacrifice. The interpretation of al-Manar highlights the spiritual education of the family of Imran, while al-Munir emphasizes the steadfastness of faith and obedience in the family of Ibrahim through the story of the sacrifice of Ismail.